Future metaphysics - Avanessian, Armen 1973- (Polity, 2020)
"This book is an attempt at restating the importance of the great metaphysical categories of substance and accident, form and matter, life and death for the present: how our contemporary predicament forces us both to reclaim them and to give them a radically new twist"--
Includes bibliographical references and index
Keywords: Substanz; Akzidens; Philosophie; Spekulation; Metaphysik; Metaphysics